2022
DOI: 10.1136/bmjgh-2021-007662
|View full text |Cite
|
Sign up to set email alerts
|

Estimating need and coverage for five priority assistive products: a systematic review of global population-based research

Abstract: IntroductionTo improve access to assistive products (APs) globally, data must be available to inform evidence-based decision-making, policy development and evaluation, and market-shaping interventions.MethodsThis systematic review was undertaken to identify studies presenting population-based estimates of need and coverage for five APs (hearing aids, limb prostheses, wheelchairs, glasses and personal digital assistants) grouped by four functional domains (hearing, mobility, vision and cognition).ResultsData in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 199 publications
(238 reference statements)
0
8
0
Order By: Relevance
“…Fifth, when using the WG questions in service/AP need surveys, consideration could be given to ask about the presence of functional difficulties without the use of assistance or APs. For example, Danemayer et al’s systematic review recommended AP indicators of total need and met need, as well as unmet and undermet need for service/AP need, are collected in population-based surveys [ 50 ]. To collect these data, a first-stage screening would also need to capture people who are using services/APs who could then undergo impairment assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, when using the WG questions in service/AP need surveys, consideration could be given to ask about the presence of functional difficulties without the use of assistance or APs. For example, Danemayer et al’s systematic review recommended AP indicators of total need and met need, as well as unmet and undermet need for service/AP need, are collected in population-based surveys [ 50 ]. To collect these data, a first-stage screening would also need to capture people who are using services/APs who could then undergo impairment assessment.…”
Section: Discussionmentioning
confidence: 99%
“…seeing, hearing, walking, remembering) and most have four response options on level of difficulty experienced in performing each activity (none, some, a lot, cannot do). People were defined as having a disability if they reported "a lot of difficulty" or "cannot do at all" for at least one question or experienced "daily" symptoms of anxiety or depression at an intensity described as "a lot" (adults 18+; "daily" symptoms for children [5][6][7][8][9][10][11][12][13][14][15][16][17]. People were also defined as having a disability if they received the Disability Allowance or reported a health condition that made them eligible for the Disability Allowance (e.g.…”
Section: Plos Onementioning
confidence: 99%
“…Poor availability, quality and affordability of services can lead to unmet needs for many people with disabilities, resulting in worsening health and functioning [ 2 ]. These gaps may be particularly pronounced for people with disabilities living in rural areas, or with certain types of impairments [ 4 , 6 , 7 ]. They may also incur higher healthcare costs, as they may need to seek care more often and incur additional costs in doing so (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic [ 21 ] and scoping reviews [ 18 , 22 ] have identified that most research publications on AT access are single-wave cross-sectional studies, which lack follow-up and inhibit the exploration of trends in this sector. Only ten studies were identified in a large systematic review that had any longitudinal/follow-up consideration, comprising <5% of all 207 included studies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic [ 21 ] and scoping reviews [ 18 , 22 ] have identified that most research publications on AT access are single-wave cross-sectional studies, which lack follow-up and inhibit the exploration of trends in this sector. Only ten studies were identified in a large systematic review that had any longitudinal/follow-up consideration, comprising <5% of all 207 included studies [ 21 ]. However, a wealth of standardised longitudinal data do exist in the forms of repeated cross-sectional administrative surveys and population cohort studies, where questions on AT are incorporated.…”
Section: Introductionmentioning
confidence: 99%